Budaya Patriarki Di Indonesia Dalam Perspektif Hukum Keluarga Islam - Handro Kurnia Sitorus; Alwi Setiawati; Balqis Vifania; Nabila Mahrani; Muhammad Yasir (Tabayyun : Journal Of Islamic Studies, 2024)
The Islamic family paradigm does not essentially differentiate between husband and wife. A wife has the same rights towards her partner as her husband does towards himself. The husband and wife relationship is equal. Husband and wife do not need to be treated equally just because they are equal in the household. Gender prejudice is truly created when husbands and wives are treated equally in all situations. Aligning men and wives in terms of household work: in one scenario, for example, husbands have an obligation to take care of their children, just like women. This means that the wife's task of caring for children is a joint responsibility, not her sole responsibility. To create an equal partnership between husband and wife, a functional relationship must be built, namely a complementary relationship based on roles and functions, not a structural relationship such as between superiors and subordinates.